Yersinia enterocolitica Septicemia After Chitterling Ingestion in a Pediatric Patient With Iron Overload Disease: A Case Report. (23rd June 2015) - Moon, Tara D.; Ma, Steven; Sheram, Mary Lynn
Yersinia enterocolitica is a gram-negative cocobacillus causing a range of illness from self-limited enteritis to invasive disease, including septicemia. It is a particularly virulent pathogen in patients with underlying hemoglobinopathies who are predisposed to iron overload. A substantial risk factor for disease in children and infants is exposure to the household preparation of chitterlings. Early identification of these patients is critical in the pediatric intensive care unit as this cause of septicemia can be missed with the potential for significant morbidity. We report an interesting case of Yersinia septicemia in a patient with iron overload disease from chitterling ingestion managed in the pediatric intensive care unit.